Reconfiguring Indonesia's Economic Policy: A Comprehensive Analysis Of The Covid-19 Pandemic Response And The Transition To Post-Crisis Policy Equilibrium - Moch. Fauzie Said; Novy Setia Yunas; Mochammad Alexander Mujiburrohman (Magister Ilmu Administrasi Publik, 2026)
This study aims to evaluate the Indonesian government’s economic policies during the COVID-19 pandemic and the post-pandemic period, with a focus on their effectiveness, adaptability, and implications for achieving a new policy equilibrium. The analysis is essential to understand how fiscal, monetary, social, and digital policy responses mitigated the crisis while simultaneously shaping a more sustainable policy configuration. The research employs a qualitative approach, combining policy analysis with a systematic literature review of reputable journals, international institutional reports, and macroeconomic data from 2020 to 2024. The study includes the interpretation of policy tables, a risk policy matrix, and the integration of public policy theories, particularly from the perspectives of policy design and policy feedback. The findings reveal that policies such as the National Economic Recovery Program (PEN), Cash Social Assistance (BST), the Job Creation Omnibus Law, and accelerated digitalization were effective in cushioning economic contraction, expanding social protection, and fostering digital transformation. However, challenges remain, including risks to monetary credibility due to burden sharing, inaccuracies in social protection targeting, and persistent digital divides in remote areas. The novelty of this study lies in its comprehensive analysis that not only assesses short-term effectiveness but also highlights the transition toward a new policy equilibrium as a post-crisis policy configuration. The results demonstrate that Indonesia has established more flexible fiscal and monetary governance, expanded its social protection architecture, and normalized economic digitalization; however, structural reforms are required to ensure inclusiveness and long-term sustainability.